A Rigorous Approach to the Teaching of Reading? Systematic Synthetic Phonics in Initial Teacher Education - Glazzard, Jonathan; Stones, Samuel (Frontiers in Education, 2020)
Abstract • This paper argues that no single method of teaching children to read is superior to any other. Although research suggests that a systematic approach to phonics produces gains in word reading and spelling, there is no clear evidence that synthetic phonics is the most effective approach for supporting reading development. • We highlight the current policy allegiance to synthetic phonics in England. This approach is mandated in the teachers’ standards and the inspection framework for initial teacher education in England. • This attempt to regulate the way new teachers are prepared to support children’s reading development is extremely concerning, given the body of research which demonstrates that no single approach is necessarily more effective than another.